Rhizobacteria as Biological Agents in Enhancing the Viability and Vigor of Rice Seeds (Oryza sativa L.) - Kadek Pande Prasetia Wiguna, I; Ayu Kade Sutariati, Gusti; Corina Rakian, Tresjia (International Journal of Science, Technology & Management, 2025)
This study aims to examine the effectiveness of rhizobacteria in stimulating plant growth and acting as a biofertilizer that can enhance the viability and vigor of rice (Oryza sativa L.) seeds. The research was conducted at the Agronomy Unit Laboratory, Faculty of Agriculture, Halu Oleo University, from September to October 2024. The study was designed based on a randomized block design (RBD), consisting of 11 test isolates and 1 control. These isolates were tested for their effectiveness in improving the viability and vigor of rice (Oryza sativa L.). The test was carried out by soaking seeds in a rhizobacteria suspension, then germinating the seeds using a standard germination procedure. The observed variables included germination capacity, vigor index, seed uniformity, relative growth rate, and T50. The results showed that seed treatment with rhizobacteria significantly increased the viability and vigor of rice seeds (Oryza sativa L.), as seen in the variables of germination capacity, vigor index, T50, and relative growth rate. From this study, 2 isolates were selected that have the potential as growth promoters for rice seeds, namely DMW 4 and DSS 3. Further research is needed to test the effectiveness of these isolates in improving the growth and yield of rice (Oryza sativa L.) under field conditions.